PORNOAKSI DALAM HUKUM POSITIF PERSPEKTIF HUKUM PIDANA ISLAM - Aisa, Nora; Rozzi, Fakhlur (TAHKIM, 2025)
This research is motivated by the fact that pornography, as regulated by positive law, is limited to acts that display nudity in public, whereas in Islamic law it is not limited and is considered a sinful act. Given the limitation of pornography in positive law and the lack of such restrictions in Islamic law, this paper aims to analyze the perspective of Islamic criminal law on the crime of pornography in positive law. This research is qualitative. The focus of this research is the perspective of Islamic criminal law on the crime of pornography in positive law. The reasons are: first, because Islamic law does not regulate the criteria for pornography. Second, in positive law, pornography is limited to acts that display nudity and other acts that lead to pornography. The results of this research conclude that the criteria for pornography are regulated in Law No. 44 of 2008, Article 10, and are included in the category of ta'zir crimes because they are regulated in a law enacted by an authorized official or ulil amri. Keywords: pornoaction, Islamic criminal law